2008
DOI: 10.1645/ge-1474.1
|View full text |Cite
|
Sign up to set email alerts
|

Sem and Tem Study of the Armed Male Terminal Genitalia of the Tapeworm Paraechinophallus japonicus (Cestoda: Bothriocephalidea)

Abstract: For the first time, the ultrastructure of the armed cirrus of an echinophallid cestode, Paraechinophallus japonicus (Yamaguti, 1934), has been studied with the use of scanning and transmission electron microscopy. Two sets of eversible copulatory organs (approximately 300 microm in length and approximately 130 microm in width) are present on the dorsal side of each segment near the lateral margin of the strobila. Except for the terminal portion, the cirrus is covered with large spines (up to 40 mircom long, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Both taxa found in Centrolophus possess the features that may represent synapomorphies of the family, i.e. a sublateral genital pore, the cirrus armed with spines (Levron et al 2008), and posterolateral margins of segments lined with a band of large spiniform microtriches (Bray et al 1994. However, the monophyly of the Echinophallidae has not been confirmed by molecular data (Brabec et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Both taxa found in Centrolophus possess the features that may represent synapomorphies of the family, i.e. a sublateral genital pore, the cirrus armed with spines (Levron et al 2008), and posterolateral margins of segments lined with a band of large spiniform microtriches (Bray et al 1994. However, the monophyly of the Echinophallidae has not been confirmed by molecular data (Brabec et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, in two members of the bothriocephalidean family Echinophallidae the cirrus sac wall consists of two independent bands of muscles, an inner one including numerous layers of longitudinal muscles and an outer band of circular muscles (Levron et al, 2008;Poddubnaya & Mackiewicz, 2009). It should be emphasized that numerous cell bodies of the muscle cells are localised within the sac wall of these 'lower' tapeworms between the muscle fibres (Poddubnaya et al, 2003(Poddubnaya et al, , 2005Poddubnaya & Mackiewicz, 2009).…”
Section: The Cirrus Sac Wall Of the Tapewormsmentioning
confidence: 99%
“…They are more typical of cyclophyllidean tapeworms and bothriocephalideans of the family Echinophallidae (Schmidt, 1986;Khalil et al, 1994). To date, there are only three TEM ultrastructural studies dealing with these sclerotized structures of the male terminal genitalia (Levron et al, 2008;Poddubnaya & Mackiewicz, 2009;present study). In the case echinophallideans (Levron et al, 2008;Poddubnaya & Mackiewicz, 2009) and cyclophyllidean Shipleya inermis (present study), the hooks of the cirrus have been identified as intracellular structures of the epithelial wall of the cirrus, which is consistent with the epithelial localization of the hooks.…”
Section: Cirrus Armature In the Eucestodamentioning
confidence: 99%
See 1 more Smart Citation
“…Bray et al (1994) placed Glossobothrium in the Echinophallidae because they synonymised the Parabothriocephalidae with the Echinophallidae, the genus having been placed in the Parabothriocephalidae by Yamaguti (1959). However, Glossobothrium is considered here to belong to the Triaenophoridae because it possesses a lateral genital pore, the cirrus is armed with small microtriches rather than with large spines (see Levron et al, 2008a), and the posterior margin of segments is not covered with the blade-like spiniform microtriches present in most echinophallids Levron et al, 2008b).…”
Section: Diagnoses Of the Genera Of The Bothriocephalideamentioning
confidence: 99%